Evaluación del desempeño docente en Chile: percepción de profesores mal evaluados - Sepúlveda Obreque, Alejandro; Hernández-Mosqueira, Claudio; Peña-Troncoso, Sebastián; Troyano Agredo, Maura Angelica; Opazo Salvatierra, Margarita
This study is linked to teacher evaluation. Its objective was to determine the factors that, according to teachers of basic education in the municipality of Osorno, affected the outcome of their teacher assessment 2015 and 2016. A written interview with open questions was applied to poorly evaluated teachers. Among the results, it was found that the operational way of dealing with the evaluation was individual, without the support of peers or consultants. They had little time for preparation. They assume an excess of confidence, reflected in the fact that they gave little importance to the process. They recognize feeling a deep disappointment, insecurity, accompanied by feelings of frustration, a mixture of emotions accentuated by the disloyalty with which their colleagues acted. They state that they did not receive support or understanding in the face of poor results, an attitude that, in their opinion, constitutes the most negative emotional burden of this evaluation process.